2019
DOI: 10.18006/2019.7(5).489.493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Textile Wastewater Irrigation on Soil Properties in Western Rajasthan

Abstract: The current research is focused on the evaluation of physico-chemical properties of soil. Textile industries of Jodhpur and Balotra cities of Western Rajasthan discharge plenty of pollutants that get mixed up with water bodies. These water bodies are basically the parts of Jojari and Luni Rivers. The soil sites near to the end points or nearby points of these rivers became polluted due to mixing of industrial effluents coming from textile industries located nearby these rivers. When same wastewater is used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…(Rathore, 2011). Shellina Khan, Navneet Joshi (2019) reported that Textile industries of Jodhpur and Balotra cities of Western Rajasthan discharge plenty of pollutants that get mixed up with water bodies. Hence, it can be conclude that the concentration of effluents affects the soil quality.…”
Section: Introductionmentioning
confidence: 99%
“…(Rathore, 2011). Shellina Khan, Navneet Joshi (2019) reported that Textile industries of Jodhpur and Balotra cities of Western Rajasthan discharge plenty of pollutants that get mixed up with water bodies. Hence, it can be conclude that the concentration of effluents affects the soil quality.…”
Section: Introductionmentioning
confidence: 99%